2016
DOI: 10.1177/000313481608200515
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Perforations by Metallic Grill Brush Bristles: Clinical Presentations and Opportunity for Prevention

Abstract: Increasing reports on the incidental ingestion of metallic bristles from barbeque grill cleaning brushes have been reported. We sought to describe the clinical presentation and grilling habits of patients presenting after ingesting metallic bristles in an attempt to identify risk factors. We performed a chart review of six patients with documented enteric injury from metallic bristles. Subjects were contacted and administered a survey focused on the events surrounding the bristle ingestion. We arranged for in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…[2][3][4] Although this pain may begin immediately at the time of eating, the onset of pain may also be delayed and has been shown to develop up to 14 days after ingestion of the foreign bodies. 1 Patients with delayed onset of pain, such as the patient described here, may have greater difficulty associating their pain with having eaten grilled meat, and such cases may be more difficult to diagnose at initial presentation. Although metal foreign bodies can be detected with both CT and abdominal radiography, CT without oral contrast enhancement is recommended for identification of metal barbeque brush bristles in patients who present with abdominal pain.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[2][3][4] Although this pain may begin immediately at the time of eating, the onset of pain may also be delayed and has been shown to develop up to 14 days after ingestion of the foreign bodies. 1 Patients with delayed onset of pain, such as the patient described here, may have greater difficulty associating their pain with having eaten grilled meat, and such cases may be more difficult to diagnose at initial presentation. Although metal foreign bodies can be detected with both CT and abdominal radiography, CT without oral contrast enhancement is recommended for identification of metal barbeque brush bristles in patients who present with abdominal pain.…”
Section: Discussionmentioning
confidence: 85%
“…If ingested, the metal bristles may cause injury to and/or perforate the gastrointestinal tract, which can lead to severe complications. [1][2][3][4][5] Health Canada, the Centers for Disease Control and Prevention, and the media have made an effort to report cases of injury and inform the public of this problem. 3,6,7 How-ever, it is also important that physicians are aware of the clinical presentation, radiologic findings, and management options associated with injuries related to ingested metal barbeque brush bristles to ensure that patients with such injuries receive efficient diagnosis and treatment, especially in the summer months during barbeque season.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic search was performed per the PRISMA literature selection process ( Figure 1 ). 2-9,12-75 Two authors (N.M. and Y.M.) independently searched the literature for relevant articles.…”
Section: Methodsmentioning
confidence: 99%
“…A literature review via PubMed revealed 14 articles about the hazards of metal bristle brushes. 1 -3 Sordo et al described 6 patients who had accidental ingestions of metallic bristles from the barbeque grill. Three of their patients underwent laparoscopic enterorrhaphy, 2 underwent laparotomy, and 1 passed the bristle without surgical intervention.…”
Section: Case Reportmentioning
confidence: 99%
“…Article reuse guidelines: sagepub.com/journals-permissions DOI: 10.1177/0145561318824220 journals.sagepub.com/home/ear the bristle without surgical intervention. 1 The Center for Disease Control and Prevention (CDC) described 6 adult patients (5 males and 1 female) who experienced ingestion of wire brush bristles causing injuries that ranged from puncture of the soft tissues of the neck, resulting in severe odynophagia, to perforation of the gastrointestinal tract, resulting in emergent surgery. The CDC recommended carefully examining the surface of the grill before cooking on it, as well as considering alternative grill-cleaning methods.…”
mentioning
confidence: 99%